APPLICATION OF THE C4.5 ALGORITHM IN MEASURING CUSTOMER SATISFACTION LEVELS TOWARD SERVICE IN A MINIMARKET - Harkamsyah Andrianof; Aggy Pramana Gusman; Okta Andrica Putra Gusman (Jurnal Sains Informatika Terapan, 2026)
Customer satisfaction is a crucial indicator in assessing the service quality of a retail business, specifically at Minimarket Berkah Jaya. Currently, customer satisfaction measurement is conducted manually, resulting in subjective and unstructured data, which hinders management from evaluating and improving service quality effectively. Therefore, this study aims to apply the C4.5 algorithm to measure and classify the level of customer satisfaction. The research data were collected through questionnaires distributed to 50 customers. The classification process used the C4.5 algorithm with attributes: Cashier Service, Shop Assistant Service, Product Completeness, Transaction Speed, and Store Facilities. The algorithm constructed a decision tree based on entropy and information gain calculations. The results indicate that Cashier Service is the most influential factor in determining customer satisfaction at Minimarket Berkah Jaya. The developed system assists management in data-driven decision-making to enhance service quality.